2017
DOI: 10.18203/2320-1770.ijrcog20173497
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of misoprostol sublingually and dinoprostone gel intracervically for cervical ripening and induction of labor

Abstract: Background: Both Prostaglandin E1 and E2 analog are being used for cervical ripening. The aims of study was to compare the efficacy and safety profile of sublingual misoprostol (PGE2) and intracervical dinoprostone (PGE1) for cervical ripening and induction of labor.Methods: One hundred women with single live fetus and with gestational age of more than 37 weeks admitted for induction of labor were recruited for the study. Patients were randomized to receive either 25μg of misoprostol sublingually or dinaprosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…[22] In Lamichhane et al's study, most common indication for LSCS was failed induction (44%) and the second common was fetal distress (29%), whereas in our study, similar indications for LSCS were observed. [14] Yadav and Chandwaskar study showed that fetal distress observed in PGE 2 (16%) was more than PGE 1 (6%), [23] whereas in our study there was no difference between the two groups. Madaan et al's study showed that dinoprostone group had significant increased rate of the cesarean section due to the fetal distress, [24] whereas in our study, 9 cases in each group had similar rates of fetal distress.…”
Section: Discussioncontrasting
confidence: 75%
“…[22] In Lamichhane et al's study, most common indication for LSCS was failed induction (44%) and the second common was fetal distress (29%), whereas in our study, similar indications for LSCS were observed. [14] Yadav and Chandwaskar study showed that fetal distress observed in PGE 2 (16%) was more than PGE 1 (6%), [23] whereas in our study there was no difference between the two groups. Madaan et al's study showed that dinoprostone group had significant increased rate of the cesarean section due to the fetal distress, [24] whereas in our study, 9 cases in each group had similar rates of fetal distress.…”
Section: Discussioncontrasting
confidence: 75%
“…Similar results were seen in study in 2003 by Agarwal et 7 where it was (12.8±6.4hrs v/s 18.53±8.5hrs) and in study in 2017 by Yadav S et al (5.39±2.97hrs vs 10.88±7.33hrs respectively). 8 In 2003 Garry D et al and in 2014 Liu A et al, also concluded in his study that interval between from start of induction to vaginal delivery was significantly shorter in Misoprostol group. 9,10 Thus Misoprostol reduces the mean duration of labour (Table 4) which reduces the duration of suffering of a patient in labour and also provides fast delivery.…”
Section: Discussionmentioning
confidence: 88%